War is not over when it's over women speak out from the ruins of war - Jones, Ann 1937- (New York Metropolitan Books, 2010)
In 2007, the International Rescue Committee, which brings relief to countries in the wake of war, wanted to understand what really happened to women in war zones. Answers came through the point and click of a digital camera. On behalf of the IRC, Ann Jones spent two years traveling through Africa, East Asia, and the Middle East, giving cameras to women who had no other means of telling the world what war had done to their lives.
Introduction: war is not healthy -- Cote d'Ivoire: "Grace a l'appareil" -- Liberia: "Life can change-- " -- Sierra Leone: girls -- The Democratic Republic of the Congo: rape -- Burmese refugees in Thailand: someplace else -- Iraqi refugees in Jordan, Syria, Lebanon: blown apart -- Afterword: it's not over.
Includes bibliographical references and index.
UCWS-2999g donated by Adrienne Maguddayao - May 2017
Keywords: Women and war; War victims; Victims of violent crimes; Women -- Violence against